1995
DOI: 10.1111/j.1476-5381.1995.tb16657.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the ETA/ETB receptor antagonist, bosentan on endothelin‐1‐induced myocardial ischaemia and oedema in the rat

Abstract: 1 The purposes of this study were to assess the role of ETB receptors in mediating endothelin-1 (ET-l)-induced myocardial ischaemia and oedema in rats and to study the inhibitory action of the novel nonpeptide ETA/ETB receptor antagonist, bosentan on these actions of ET-1. 2 Intravenous bolus injection of ET-1 (1 nmol kg-') into anaesthetized rats produced marked ST segment elevation of the electrocardiogram without causing arrhythmias. ST segment elevation developed within 30-50 s and persisted for at least 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The present results showing that verapamil and nifedipine markedly, though not completely, protected the heart from ST segment elevation elicited by either ET-1 or IRL 1620, confirm and extend these observations. The pro-ischaemic action of IRL 1620 was unaffected by the ETA receptor-selective antagonist, FR 139317, but was completely prevented by the ETA/ETB antagonist bosentan (Filep et al, 1995), indicating that under the present experimental conditions, IRL 1620 selectively activated ETB receptors. Our data would also indicate that ETA as well as the constrictor ETB (ETB2) receptor subtypes involved in mediating ST segment elevation in the rat heart are coupled to activation of voltage-gated calcium channels.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The present results showing that verapamil and nifedipine markedly, though not completely, protected the heart from ST segment elevation elicited by either ET-1 or IRL 1620, confirm and extend these observations. The pro-ischaemic action of IRL 1620 was unaffected by the ETA receptor-selective antagonist, FR 139317, but was completely prevented by the ETA/ETB antagonist bosentan (Filep et al, 1995), indicating that under the present experimental conditions, IRL 1620 selectively activated ETB receptors. Our data would also indicate that ETA as well as the constrictor ETB (ETB2) receptor subtypes involved in mediating ST segment elevation in the rat heart are coupled to activation of voltage-gated calcium channels.…”
Section: Resultsmentioning
confidence: 61%
“…Therefore, the absence of arrhythmias in our experiments would indicate that ET-1 and IRL 1620 acted primarily on the coronary vascular smooth muscle rather than on the myocardium. Previous studies have shown that in addition to ETA receptors, ETB receptors also mediate the vasoconstrictor (Clozel et al, 1992;Teerlink et al, 1994) and pro-ischaemic effects (Filep et al, 1995) of ET-1 in the rat coronary circulation. ET-1-induced contraction of coronary arteries and ST segment elevation can be attenuated by calcium antagonists (Kim et al, 1989;Turner et al, 1989;Suzuki et al, 1992;Harada et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…These data show that similarities and differences in activity in vitro are borne out in vivo, at least for the nanoparticles tested. Although an increase in monocytes (such as that induced by Qdot-NH 2 -PEG) has been associated with toxic exposures (22,23), further studies are needed to clarify if the changes in monocyte level after Qdot-NH 2 -PEG exposure correlate with other immune or adverse phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to examine the in vivo effects of these nanoparticles on the monocyte population after a brief exposure for a number of reasons: (i) alterations in leukocyte subsets, including increased monocyte fraction, can be a sign of proinflammatory or other toxic exposures (22,23), (ii) monocytes are phagocytic, and take up certain nanoparticles more than many other cell types (14), and (iii) nanomaterials have been shown to cause pleiotropic effects on immune cells that are very sensitive to the materials' composition and surface (24). Full details may be found in Table S1.…”
Section: In Vitro Relationships Among Nanoparticles Correlate With Inmentioning
confidence: 99%
“…Bosentan, a nonselective ET receptor antagonist, was given i.v. 20 minutes before AZ2 infusion start at a dose of 15 mg/kg, based on the reported ability to markedly suppress the pressor effect of exogenously administered ET-1 (63). Phentolamine, the nonselective α-AR antagonist, was administered i.v.…”
Section: Synthesismentioning
confidence: 99%